2014
DOI: 10.1007/s11557-014-1020-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers delimit cryptic species in Ceratocystis sensu stricto

Abstract: Ceratocystis sensu stricto is a genus of closely related fungi that are mostly plant pathogens. Morphological variation between species in this genus is limited, and species delineation is strongly reliant on phylogenetic inference. Primary support for many of the species is based on the ITS region which, on its own, can be used to delineate all species described in the genus. However, the recent discovery of two ITS types in a single isolate of Ceratocystis questions the use of this marker in taxonomic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 63 publications
1
95
0
1
Order By: Relevance
“…When species concepts alternative to the genealogical concordance phylogenetic concept are considered, these isolates could be seen as different haplotypes of C. fimbriata (Oliveira et al, 2015). However, based on previous phylogenetic analyses including five gene regions (Fourie et al, 2014) we consider C. manginecans as a species distinct from the sweet potato black rot fungus which includes the type of C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When species concepts alternative to the genealogical concordance phylogenetic concept are considered, these isolates could be seen as different haplotypes of C. fimbriata (Oliveira et al, 2015). However, based on previous phylogenetic analyses including five gene regions (Fourie et al, 2014) we consider C. manginecans as a species distinct from the sweet potato black rot fungus which includes the type of C.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences obtained were aligned to previously generated data sets of the ITS and βT 1 regions, respectively, of C. fimbriata sensu stricto (Fourie et al, 2014). Alignments were performed using MUSCLE in MEGA v. 5 (Tamura et al, 2011) and used to construct phylogenetic trees of ITS and βT 1 based on Maximum parsimony (MP).…”
Section: Sequence Alignment and Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There are only six previous reports of Ceratocystis species from China and all species reside in the South American Clade. These species include C. manginecans from recently harvested stumps of Eucalyptus in GuangDong Province (Chen et al 2013;Fourie et al 2015), and C. fimbriata s.l, causing a disease on Eucalyptus (Li et al 2014b), Ipomoea batatas (sweet potato; Sy 1956), Punica granatum (pomegranate; Huang et al 2003;Xu et al 2011), Colocasia esculenta (taro; Huang et al 2008) and Eriobotrya japonica (loquat; Li et al 2014a). Considering the number of Ceratocystis species found in other countries, and the small number of studies on species of Ceratocystis and other Ceratocystidaceae found in China, the discovery of C. cercfabiensis and C. collisensis suggests that many other species in the genus and family remain to be discovered in this geographic area.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the delimitation of species in the South American Clade lack sufficient markers for their clear delimitation (Al Adawi et al 2013;Harrington et al 2014;Fourie et al 2015). The ITS region, which has been selected as the universal barcoding region for fungal species (Schoch et al 2012), has been shown to be present as multiple ITS types in single isolates of some Ceratocystis species (Al Adawi et al 2013;Naidoo et al 2013;Harrington et al 2014).…”
Section: Introductionmentioning
confidence: 99%